(untitled) (Acta Entomologica Serbica, 2018)
A faunal study on plant bugs (Miridae) was carried out in the western part of Kurdistan province during 2016-2017. Two species of the genus Brachycoleus Fieber, 1858 were collected: B. thoracicus Puton, 1892 and B. lineellus Jakovlev, 1884. The former species is reported for the first time from Iran and the latter for the first time from Kurdistan province. In this study, a description of B. thoracicus, and habitus photographs of male and female B. thoracicus Puton, 1892 and B. lineellus Jakovlev are provided. The identified specimens were deposited in the insect collection of the Natural History Museum at University of Guilan, Rasht, Iran.